Antioxidant dietary fiber isolated from spent coffee (Coffea arabica L.) grounds improves chronotype and circadian locomotor activity in young adults. Issue 8 (10th July 2019) - Oseguera-Castro, Karla Y.; Madrid, Juan A.; Martínez Madrid, María José; García, Olga P.; del Castillo, Maria Dolores; Campos-Vega, Rocio
Abstract : This study shows for the first time, the modulation of the circadian rhythm and the positive chronobiotic effects of humans, by a dietary intervention, in daily life, with food or dietary fiber source. Abstract : Chrononutrition, or the circadian timing of food intake, proposes that nutrients, bioactive compounds, and foods modulate the peripheral clocks with implications on health. We evaluated the effects of biscuits supplemented with the antioxidant dietary fiber isolated from spent coffee grounds as a food ingredient (SCF-B) or a combination of spent coffee grounds and fructooligosaccharides (SC-FOS-B), and a traditional recipe (TB, without added fiber) on the modulation of circadian rhythm in young adults. The repeated intake (21 days/45 g portion) of SCF-B or SC-FOS-B decreased ( p < 0.05) the evening chronotypes. SCF-B and SC-FOS-B consumption enhanced the chronodisruption associated with colonic short chain fatty acid production, thus improving the quality and length of sleep. This is the first study on the positive impact of antioxidant dietary fiber obtained from spent coffee grounds on circadian activity improvement in young adults. Further clinical trials and the role of other bioactive compounds as therapeutic candidates for health disturbances related to circadian dysfunction are necessary to confirm the results.